ANALISIS TINGKAT KEKUMUHAN DAN PENINGKATAN PERMUKIMAN PESISIR DI DESA TOROKEKU KECAMATAN TINANGGEA KABUPATEN KONAWE SELATAN - Sutrisno Sutrisno; Andi Irwan; Muh. Ramli (Jurnal Perencanaan Wilayah, 2019)
This study aims to analyze: (1) the level of slums in coastal settlements in South Konawe Regency,(2) efforts to improve the quality of coastal settlements in this Regency. This research was conducted inTorokeku Village, Tinanggea Sub-District, South Konawe Regency. This study uses a quantitative descriptionmethod, and the data was obtained through observation, interviews, and literature studies. The analysis wascarried out by using a location assessment formula based on Minister of Public Works and HousingRegulation No. 02 of 2016 by considering eight criteria: (1) Condition of residential buildings, (2)Environmental road conditions, (3) Clean water supply conditions, (4) Conditions for wastewater treatment,(5) Condition of waste treatment, (6) Fire protection conditions, (7) Coastal environmental conditions and(8) Coastal disaster risk conditions.Based on the results of the analysis, the slum level of coastal settlements in Torokeku Village fallsinto the category of moderate slums. This is caused by the condition of high building density and the numberof uninhabitable houses, damaged road conditions and not yet reaching all the houses, unsufficient cleanwater for the community, the absence of waste water treatment facilities, the absence of waste processing, theabsence of fire protection facilities and the reduction of the mangrov ecosystem. Improving the quality ofsettlements is carried out through rehabilitation and home development in new locations; repairment andimprovement of public facilities and infrastructure such as environmental roads, clean water, waste watertreatment, waste treatment, and fire protection facility; and through the restoration the damage mangrovecosystem.Key words: Level of Slumness, Quality Improvement, Coastal Settlement